2001
DOI: 10.1161/01.hyp.37.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Y-Chromosome Transfer Induces Changes in Blood Pressure and Blood Lipids in SHR

Abstract: Abstract-Previous studies with chromosome-Y consomic strains of spontaneously hypertensive rats (SHR) andWistar-Kyoto rats suggest that a quantitative trait locus for blood pressure regulation exists on chromosome Y. To test this hypothesis in the SHR-Brown Norway (BN) model and to study the effects of chromosome Y on lipid and carbohydrate metabolism, we produced a new consomic strain of SHR carrying the Y chromosome transferred from the BN rat. We found that replacing the SHR Y chromosome with the BN Y chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
(45 reference statements)
3
22
0
Order By: Relevance
“…Results based on the chromosome Y consomic strains derived from SHR and WKY rats have suggested the possible effect of Y chromosome on determination of BP (8)(9)(10)(11). It can be speculated that sexual dimorphism in cardiovascular risk can be partly explained by the effect of the Y chromosome, and polymorphisms within the male specific non-recombining region of the Y chromosome are linked to increased cardiovascular risk in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results based on the chromosome Y consomic strains derived from SHR and WKY rats have suggested the possible effect of Y chromosome on determination of BP (8)(9)(10)(11). It can be speculated that sexual dimorphism in cardiovascular risk can be partly explained by the effect of the Y chromosome, and polymorphisms within the male specific non-recombining region of the Y chromosome are linked to increased cardiovascular risk in men.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the Y chromosome consomic strains derived from spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY) revealed the possible effect of the Y chromosome on determination of blood pressure (BP), with an SHR Y chromosome in a WKY genetic background exerting the BP-elevating effect (8)(9)(10). Similarly, replacement of the SHR Y chromosome with that of Brown Norway rats has been associated with significant reduction in both SBP and DBP (11).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies examined the impact of a high-fat/high-cholesterol diet on serum lipids. 29,39,40 To the best of our knowledge, however, the effect of HFD on adiposity and BP has not been compared between SHR and BN. It has been demonstrated, though, that SHR compared with other normotensive strains, namely, Wistar-Kyoto or Sprague-Dawley rats, are resistant to weight gain in response to HFD feeding; they either do not increase BW 41 or increase it less than does the normotensive strain.…”
Section: Discussionmentioning
confidence: 99%
“…2 Extensive data from rodent models indicate a significant association between the Y chromosome and BP. [3][4][5][6][7][8] Moreover, human studies have shown that a hypertensive father but not a mother affects BP in normotensive male offspring. 9 Recently, Ellis et al 10 reported an association between an increased risk of elevated diastolic blood pressure (DBP) and a biallelic polymorphism on the NRY region of the Y chromosome in 409 subjects recruited from the general population in Victoria, Australia.…”
mentioning
confidence: 99%